Dragging Wyatt Earp : a personal history of Dodge City - Rebein, Robert, 1964- (Swallow Press, 2013)
In this book, an essayist explores what it means to grow up in, leave, and ultimately return to the iconic Western town of Dodge City, Kansas. In chapters ranging from memoir to reportage to revisionist history, the writer contrasts his hometown's Old West heritage with a New West reality that includes salvage yards, beefpacking plants, and bored teenagers cruising up and down Wyatt Earp Boulevard. Along the way, the author covers a vast expanse of place and time and revisits a number of Western myths, including those surrounding Francisco Vasquez de Coronado, the Cheyenne chief Black Kettle, George Armstrong Custer, and - of course - Wyatt Earp himself. The writer rides a bronc in a rodeo, spends a day as a pen rider at a local feedlot, and attempts to "buck the tiger" at Dodge City's Boot Hill Casino and Resort. This book is an exciting entry in what is sometimes called the nonfiction of place.